2010
DOI: 10.1152/ajpheart.00571.2009
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide is not obligatory for radial artery flow-mediated dilation following release of 5 or 10 min distal occlusion

Abstract: Pyke K, Green DJ, Weisbrod C, Best M, Dembo L, O'Driscoll G, Tschakovsky ME. Nitric oxide is not obligatory for radial artery flowmediated dilation following release of 5 or 10 min distal occlusion. Am J Physiol Heart Circ Physiol 298: H119 -H126, 2010. First published October 30, 2009 doi:10.1152/ajpheart.00571.2009.-This study investigated the nitric oxide (NO) dependence of radial artery (RA) flowmediated dilation (FMD) in response to three different reactive hyperemia (RH) shear stimulus profiles. Ten hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
76
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(86 citation statements)
references
References 37 publications
(69 reference statements)
4
76
0
6
Order By: Relevance
“…[23][24][25][26] Nonetheless, there have been some well-designed and controlled studies that have been unable to inhibit FMD using NO blockade. 27,28 This disparity in the literature may not only be related to differences in the methodology used to measure FMD, but also to the inclusion of different population groups.Therefore, the aim of this study was to systematically review and meta-analyze the literature relating to crossover studies that have compared FMD under local infusion of saline (FMD saline ) with FMD under local infusion of theto obtain an estimate of the contribution of NO to FMD in human conduit arteries. We used a staged approach and explored the contribution of NO in FMD studies that adopted the standardized approach (ie, using distal cuff placement and ≈5-minute cuff inflation in healthy individuals).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25][26] Nonetheless, there have been some well-designed and controlled studies that have been unable to inhibit FMD using NO blockade. 27,28 This disparity in the literature may not only be related to differences in the methodology used to measure FMD, but also to the inclusion of different population groups.Therefore, the aim of this study was to systematically review and meta-analyze the literature relating to crossover studies that have compared FMD under local infusion of saline (FMD saline ) with FMD under local infusion of theto obtain an estimate of the contribution of NO to FMD in human conduit arteries. We used a staged approach and explored the contribution of NO in FMD studies that adopted the standardized approach (ie, using distal cuff placement and ≈5-minute cuff inflation in healthy individuals).…”
mentioning
confidence: 99%
“…[23][24][25][26] Nonetheless, there have been some well-designed and controlled studies that have been unable to inhibit FMD using NO blockade. 27,28 This disparity in the literature may not only be related to differences in the methodology used to measure FMD, but also to the inclusion of different population groups.…”
mentioning
confidence: 99%
“…PGI2 and Relative Contribution to Flow-Mediated Dilation Doshi et al 94) found that administration of NOS inhibitor N G -monomethyl-L-arginine (L-NMMA) completely abolished FMD of the brachial artery following 5 minutes of wrist cuff occlusion, with no difference in the hyperemic stimulus; however, L-NMMA does not completely block the FMD response when the occlusion cuff is placed on the upper arm 94,95) (see Table 1). Similarly, L-NMMA does not completely abolish FMD in the radial 11,27,28,[96][97][98][99][100][101] and femoral arteries 12) . The relative importance of NO to FMD may also be altered when conducting this test on patients with a number of diseased states, such as dystonia 26) , chronic heart failure 27) or hypertension 28) (see Table 2).…”
Section: Prostacyclinmentioning
confidence: 96%
“…Furthermore, studies have shown that the proportional contribution of NO to FMD is diminished when conduit arteries are exposed to prolonged increases in shear stress. This has been demonstrated via the use of occlusion periods greater than 5 minutes, or through local hand warming 98) .…”
Section: Nitric Oxidementioning
confidence: 99%
See 1 more Smart Citation